An Integrated Approach to the Reduction of Reactive Power Losses in Radial Distribution Network - Than, Khong Hon (Universiti Teknologi Petronas, 2004)
Distribution system forms an important part of the electrical power system connecting high voltage transmission lines to low voltage consumers through feeders, distributors and service mains. Losses will occur in the distribution line due to the resistance and reactance of the cables. Consequently, this will eventually lead into voltage instability of the system. Therefore, reduction of reactive power is required to compensate the losses. The objective of this project is to compensate reactive power with appropriate methods. There are basically two commonly usedmethods: network reconfiguration and capacitor insertion. The scope of study would be on the capacitor insertion in radial distribution network. An existing algorithm will be studied and an integrated approach to the reduction ofreactive power losses will be proposed. This report will cover the progress and all findings in the two-semester final year project (FYP). This report consists of 6 main chapters where the first chapter serves as the introduction and background of the project. The next chapter is basically the literature review on all the relevant information. Methodology outlines the process flow as well as tools required for the project. The algorithm for single and multiple capacitor insertion will be introduced in Chapter 4. Chapter 5 will mainly cover on the results from the load flow simulation and results from single and multiple capacitors placement. Besides, comparison will be done between single and multiple capacitors as well as comparisons between the proposed method with the existing method. The conclusion of this report shall summarize the findings and recommendations for future project work.